Mekanisme Perhitungan Bagi Hasil Pada Produk Tabungan Haji Berbasis Akad Mudharabah - Isnawati Setyo Putri; Zahrani Aya Sofiya; Rini Irfaniyah Ziya'ul Haqque; Arin Setiyowati (Musyarakah: Journal of Sharia Economic (MJSE), 2021)
Islamic bank have three functions as fund collectors, fund distributors and services. Bank Syariah Indonesia (BSI) has a variety of product offerings, one of which is the Tabungan Haji Indonesia which is intended for customers who want to perform the pilgrimage. In the Tabungan Haji Indonesia, there is the application of sharia contracts using the Mudharabah contract. In this study using descriptive qualitative methods witd data sources collected through interviews and observations. Form the results of the study that registration for the pilgrimage can be done ehen the minimum amount of savings balance has been met and then you will be able to register with SISKOHAT. In the Tabungan Haji Indonesia product at Bank Syariah Indonesia (BSI) in the implementation of the Mudharabah contract there is a profit sharing mechanism that has been determined with the bank 96% : the customer 4%.